Civic Storytelling : The Rise of Short Forms and the Agency of Literature - Fuchs, Florian, 1984- (Book collections on Project MUSE., 2023)
"This book recalibrates literature's political role for the twenty-first century by excavating the deep history of storytelling as a civic agency"--